2018
DOI: 10.1590/01047760201824042603
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF WATER DEFICIT AND ABSCISIC ACID ON PHOTOSYNTHETIC AND ANTIOXIDANT METABOLISM IN SEEDLINGS OF Calophyllum brasiliense (CAMBESS.)

Abstract: Intermittent water defi cit decreased plant water status and gas exchange. Application of ABA preserved the photosynthetic apparatus. Antioxidant activity increased depending on the enzyme, ABA concentration and plant part.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(35 reference statements)
2
3
0
1
Order By: Relevance
“…The lower stomatal conductance (Gs) and Rubisco carboxylation rate (A/Ci) and higher internal CO 2 concentration of plants of H. courbaril under water deficit and 0% shading corroborate information in the literature in which these changes are related to variations in soil moisture due to irrigation, and in most species, reductions in gs associated with stomatal closure decrease water loss when exposed to low water availability and high insolation, while also reducing Rubisco activity (Reis et al, 2018;Bartieres et al, 2020;Freitas et al, 2020;Rosa et al, 2021;. These authors suggested that the increase of C i followed by reduction of A has been attributed to the lower rate of Rubisco carboxylation in plants under water and light stress.…”
Section: Discussionsupporting
confidence: 84%
“…The lower stomatal conductance (Gs) and Rubisco carboxylation rate (A/Ci) and higher internal CO 2 concentration of plants of H. courbaril under water deficit and 0% shading corroborate information in the literature in which these changes are related to variations in soil moisture due to irrigation, and in most species, reductions in gs associated with stomatal closure decrease water loss when exposed to low water availability and high insolation, while also reducing Rubisco activity (Reis et al, 2018;Bartieres et al, 2020;Freitas et al, 2020;Rosa et al, 2021;. These authors suggested that the increase of C i followed by reduction of A has been attributed to the lower rate of Rubisco carboxylation in plants under water and light stress.…”
Section: Discussionsupporting
confidence: 84%
“…The intercellular CO 2 concentration in plants under water restriction in P0 increased significantly, and in seedlings under 0% shading it was 3.7 times higher when compared to the other cultivation conditions, however, the values significantly reduced in Rec, which favored the increase of A/C i values especially in seedlings under 70% shading. The increase of C i on period of P0 in seedlings under water restriction is a consequence of the lower efficiency of carboxylation A/C i and gs, as observed for other tree species such as C. brasiliense (Reis et al 2018) H. courbaril (Freitas et al 2018) Schinus terebinthifolius Raddi (Nunes et al 2017).…”
Section: Discussionmentioning
confidence: 61%
“…Similarly, the activity of antioxidant enzymes increased both in the aerial parts of the plants and their roots, in response to water restriction in Schinus terebinthifolius Raddi seedlings (Nunes et al 2017). They were also observed in seedlings of C. brasiliense seedlings (Reis et al 2018), Copaifera langsdorffii Desf. (Rosa et al 2017).…”
Section: Discussionmentioning
confidence: 77%
“…The water deficit in the soil has caused metabolic changes in different species of plants [17,18]. However, with the passage of time of exposure in water deficiency conditions, plants can develop certain tolerance while maintaining breath ability for longer periods.…”
Section: V Discussionmentioning
confidence: 99%